2018
DOI: 10.1161/jaha.118.008719
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Length of Hospital Stay After Complete Repair for Tetralogy of Fallot: A Prospective Cohort Study

Abstract: BackgroundWe sought to identify patient and surgical factors associated with time to hospital discharge in patients undergoing complete repair for tetralogy of Fallot.Methods and ResultsWe performed a prospective cohort study of patients with tetralogy of Fallot admitted for complete repair between May 1, 2012 and June 2, 2017 at Children's Hospital of Philadelphia with detailed demographic, clinical, and operative characteristics. The primary outcome was time to hospital discharge. Cox proportional hazards mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 35 publications
(70 reference statements)
4
30
1
Order By: Relevance
“…In the literature, the LOHS after TOF surgical repair has been reported as six to eight days. [2,3,[9][10][11] In our study, the mean LOHS was found to be eight (range, 1.0 to 40.0) days. In a prospective study of 151 patients evaluating the factors affecting hospital stay after TOF surgical treatment, birth weight, absence or atresia of the pulmonary valve, presence of MAPCA, institution of CPB more than once, duration of arterial cross-clamp (ACC), use of circulatory arrest, neonatal repair, and the lowest hematocrit during CPB were shown to be predictors of hospital stay.…”
Section: Discussionsupporting
confidence: 45%
See 4 more Smart Citations
“…In the literature, the LOHS after TOF surgical repair has been reported as six to eight days. [2,3,[9][10][11] In our study, the mean LOHS was found to be eight (range, 1.0 to 40.0) days. In a prospective study of 151 patients evaluating the factors affecting hospital stay after TOF surgical treatment, birth weight, absence or atresia of the pulmonary valve, presence of MAPCA, institution of CPB more than once, duration of arterial cross-clamp (ACC), use of circulatory arrest, neonatal repair, and the lowest hematocrit during CPB were shown to be predictors of hospital stay.…”
Section: Discussionsupporting
confidence: 45%
“…Pulmonary annulus Z-score and operation age did not affect the hospital stay. [3] In another study, comorbid factors such as preoperative renal failure, preoperative neurological deficits, and preoperative MV dependence prolonged LOHS. [12] Kirsch et al [13] also reported that the development of low weight, chromosomal abnormalities, and complications were associated with prolonged LOHS.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations